Analysis of Differences Between Levelling Networks in the County of Hajdú-Bihar - Varga, Zsolt; Kézi, Csaba; Czédli, Herta (International Journal of Engineering and Management Sciences, 2023)
The height determination of control and detail points is essential during the process of planning and manufacturing in the practice of civil engineering. Planning maps are drawn for the former, while the intended plan is set out on the ground during manufacturing, and after the manufacturing the completed installation is mapped. Using the same reference system in all three steps, both horizontally and vertically, is recommended even though in some cases it is unavoidable to change from one reference level to another. Regardless of the fact that both refer to the mean sea level of the Baltic Sea, this can create difficulties, since the difference between the EOMA and Bendefy networks used in Hungary shows varying values depending on the geographical location. The aim of the analysis is to determine a constant difference regarding the analysed settlements based on the common points of the networks.